REHABILITATION AFTER ACL RECONSTRUCTION AND THE RISK OF SECONDARY CONTRALATERAL INJURY: A LITERATURE REVIEW OF RETURN TO SPORT TIME AND FUNCTIONAL CONTROL - Maciej Sobczyk; Weronika Stachera; Julia Stępień; Barbara Wołoszyn; Patrycja Rzeźnik; Julia Guzowska; Aleksandra Chajnowska; Aleksandra Borowy; Wiktoria Suchcicka; Małgorzata Zach (International Journal of Innovative Technologies in Social Science, 2025)
Anterior cruciate ligament (ACL) injuries are highly prevalent among athletes participating in pivoting sports and often result in functional limitations and long-term performance decline. While ipsilateral re-ruptures have been extensively studied, the risk of contralateral ACL injuries following reconstruction remains insufficiently explored. This review aimed to analyze literature published between 2020 and 2025 to investigate the relationship between rehabilitation duration and the incidence of contralateral ACL injury, as well as to propose return-to-sport (RTS) recommendations. A narrative review was conducted using PubMed, MDPI, ScienceDirect, and Google Scholar, with 20 studies meeting the inclusion criteria. These studies focused on athletic populations aged 15 to 40 years and addressed RTS timing and secondary injury outcomes. Results showed that athletes who returned to sport before nine months post-surgery had up to a fourfold increased risk of contralateral ACL injury. Key risk factors included lower limb strength asymmetry (LSI <90%), insufficient psychological readiness (ACL-RSI <70), and compensatory biomechanical patterns such as stiffer landings and altered joint loading. The findings support a minimum rehabilitation duration of 9–12 months, with RTS decisions guided by functional, psychological, and biomechanical criteria to reduce the risk of reinjury.